Modern Tibetan literature and social change - Hartley, Lauran R., 1964-; Schiaffini-Vedani, Patricia, 1967- (e-Duke books scholarly collection., 2008)
Modern Tibetan Literature and Social Change is the first systematic and detailed overview of modern Tibetan literature, which has burgeoned only in the last thirty years. This comprehensive collection brings together fourteen pioneering scholars in the nascent field of Tibetan literary studies, including authors who are active in the Tibetan literary world itself. These scholars examine the literary output of Tibetan authors writing in Tibetan, Chinese, and English, both in Tibet and the Tibetan diaspora. The contributors explore the circumstances that led to the development of modern Tibetan literature, its continuities and breaks with classical Tibetan literary forms, and the ways that writers use forms such as magical realism, satire, and humor to negotiate literary freedom within the PRC. They provide crucial information about Tibetan writers' lives in China and abroad, the social and political contexts in which they write, and the literary-critical merits of their oeuvres. Along with deep social, cultural, and political analysis, this wealth of information clarifies the complex circumstances under which Tibetan writers negotiate the realities they face in the PRC and in the diaspora. The contributors consider not only poetry, short stories, and novels but also other forms of cultural production-such as literary magazines, films, and Web sites-that provide a public forum in the Tibetan areas of the PRC, where censorship and restrictions on public gatherings remain the norm. Modern Tibetan Literature and Social Change includes a previously unavailable list of modern Tibetan works translated into Western languages and a comprehensive English-language index of names, subjects, and terms.